Toxicopathological study on the effect of different toxic doses of Euphorbia granulata F. crude extract in albino mice - AL-Naimi, Rajiha A. (The Iraqi Journal of Veterinary Medicine, 2011)
The purpose of this study was to evaluate the effect of different toxic doseswith regard to toxicopathological changes in mice injected with ethanolic crudeextract of Euphorbia granulata F. The experiment was done on (24) mice of(6-8weeks age and 20-25g weight ) divided equally into (4) groups as follows:-First group injected distilled water subcutaneously for 45 days and consideredas control ,second group injected subcutaneously (600 mg/kg B.W/day)ethanolic extract of E. granulata for 45 days, Third group injectedsubcutaneously (800 mg/kg B.W/day) ethanolic extract of E. granulata for 45days. Fourth group injected subcutaneously (1000 mg/kg B.W/day) ethanolicextract of E. granulata for 45 days.The microscopic findings of internal targetorgans revealed that the severity of the lesion increased with the dose of theplant extract. Animals injected with (1000 mg/kg B.W) showed fibrosis in liver,kidney, myocardium with encephalomalacia and aggregation of astrocytes andmicroglial cells.Furthermore the study showed mononuclear infiltrations insome internal organs, with multiple granulomatous reaction and perivascularlymphocytic cuffings. Amyloid deposition in spleen with nodular hyperplasia ofliver and hyperplasia of epithelial lining of endometrium.In conclusion, toxicdoses of ethanolic crude extract of Euphorbia granulata F cause severetoxicopathological changes in important organs and tissues in addition theactive compound of plant may act as immune stimulant, with formation ofprecancerous lesions in liver and uterus.